2016
DOI: 10.2217/nnm-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Hexametaphosphate As a Wound Care Material Coating: Antimicrobial efficacy, Toxicity and Effect on Healing

Abstract: CHX-HMP could become a useful component of wound care materials with sustained antimicrobial efficacy, lower toxicity than chlorhexidine digluconate materials, and reduction in wound colonization without affecting closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…CHX acts bactericidally by destroying bacteria cell membranes [27], and due to its antiseptic properties, it is mainly used in medicine and oral hygiene as a component in mouthwash [28]. Its antimicrobial effect in wound dressings, which was more significant for Grampositive bacteria, has also been confirmed by several studies [23,[29][30][31].…”
Section: Introductionmentioning
confidence: 91%
“…CHX acts bactericidally by destroying bacteria cell membranes [27], and due to its antiseptic properties, it is mainly used in medicine and oral hygiene as a component in mouthwash [28]. Its antimicrobial effect in wound dressings, which was more significant for Grampositive bacteria, has also been confirmed by several studies [23,[29][30][31].…”
Section: Introductionmentioning
confidence: 91%
“…Elemental analysis for C, H, N and P was carried out by the University of Bristol microanalytical laboratory. Other properties of the CHX-HMP have been reported in earlier publications [12][13][14] CHXdg alginate films were prepared as for CHX-HMP films by dissolving the alginate in CHXdg solution diluted to the required concentration, instead of the CHX-HMP suspension, and these are referred to as X-CHXdg where X again represents the concentration of CHX-HMP that provides the equivalent concentration of CHX in the material. Disk shaped specimens (ø = 10 mm) were cut from theses material and used for subsequent work.…”
Section: Synthesis and Analysis Of Chx-hmpmentioning
confidence: 99%
“…It was claimed that CHX-HMP has advantages such as sustained antimicrobial efficacy and lower toxicity than CHX digluconate materials. 171 Recently, CHX hexametaphosphate nanoparticle was successfully added into conventional GICs and it has shown as to be an effective antimicrobial agent against a wide range of oral bacteria in a dose-dependent manner. However, the diametral tensile strength decreased with substitutions of 10% and 20% NPs into GICs.…”
Section: Chlorhexidinementioning
confidence: 99%
“…For the first time, Barbour et al reported the development of novel antimicrobial NPs based on a hexametaphosphate salt of CHX. It was claimed that CHX‐HMP has advantages such as sustained antimicrobial efficacy and lower toxicity than CHX digluconate materials . Recently, CHX hexametaphosphate nanoparticle was successfully added into conventional GICs and it has shown as to be an effective antimicrobial agent against a wide range of oral bacteria in a dose‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%